Handbook for today's Catholic teen - Auer, Jim (b, 2004)
Catholic youth.
"Companion volume to ... Handbook for today's Catholic"--Back cover.
Keywords: Customs and practices -- Catholic Church; Doctrines -- Catholic Church; Handbooks, manuals etc. -- Catholic Church